PENGARUH MEDIA SOSIAL INSTAGRAM BAGI KEAKTIFAN ORANG MUDA KATOLIK DALAM HIDUP MENGGEREJA DI PAROKI SANTO PAULUS BOJONEGORO - Triawan, Hendri; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2021)
Instagram is one of the most popular digital social media and is widely used by children to adults. Young Catholics of Saint Paul Parish Bojonegoro use Instagram as a means of communication and interaction with others. This study aims to determine the influence of Instagram of young Catholics of Bojonegoro on involvement in church life. The study used a quantitative method with a random sampling technique. Data collection used Google Form. The respondents numbered 115 people, namely members of the young Catholics of Saint Paul Parish Bojonegoro who were unmarried, and aged between 13-35 years. Based on the results of the study, this Instagram account often uploads content in the form of activities with young Catholics, spiritual activities, liturgical service tasks, and covers of spiritual songs. These posts provide benefits for their followers in obtaining information and inspire them to be more actively involved in Church life.